Content-based instruction at the tertiary level an exploration / Noorzan Hj. Mohd. Noor (Universiti Teknologi MARA, Terengganu, 1992)
Many claim that a second language is learned most effectively when used as a medium to convey informational content of interest and relevance to the learner. "Contextualizing" classroom lessons has become an accepted rule of good language teaching. Yet much of the controversy about second language teaching centers around the question of what role content should play in language teaching. What, for example, is the importance of meaningful content in the language acquisition process? Are texts which have certain grammatical and discourse features more appropriate than others for particular language teaching purposes? What are the implications of using varied subject matter as opposed to developing the same theme in depth? How can a given content best be integrated with language teaching purposes in the language classroom? While the need for coordinating the learning of the language and subject-matter is recognized, just how this should be accomplished remains a problem. It is, however, clear that the task of devising a policy for the integration of language and subject area calls for the development of a more integrated model of language and content learning than presently exists. This paper is an exploration into the ways learning of the language and subject matter can be coordinated. The contemporary models of content-based instruction in use at the university level in Canada and the U.S.A. will be used as examples to detail the common philosophical features underlying the models and to differentiate them according to certain criteria such as their applicability to different settings and proficiency levels. The implication of their features on the language learning and teaching process will then be discussed.